Tough and Flexible, Super Ion‐Conductive Electrolyte Membranes for Lithium‐Based Secondary Battery Applications. (16th December 2020) - Mong, Anh Le; Shi, Qing Xuan; Jeon, Hyungjoon; Ye, Yun Sheng; Xie, Xiao Lin; Kim, Dukjoon
Abstract: Recently, stringent requirements brought on by environmental regulations and safety issues are driving the development of solid electrolytes to replace conventional liquid electrolyte systems for lithium‐based secondary batteries (LiBs). However, the low Li‐ion conductivity and/or poor mechanical properties of electrolytes remain the main obstacles hindering their commercialization. Hierarchitectural and composite polymer separators (CPSs) based on electrolyte membranes have been reported as promising tools for both high ionic conductivity and mechanical stability. In light of such work, the new types of flexible electrolytes based on phase‐separated and mixed‐phase morphologies achieved via self‐assembly and the use of functional molecular composites are reviewed along with the fundamental mechanisms associated with such systems. In particular, the structure and morphology, ionic conductivity, thermal/mechanical stability, and fabrication of polymer electrolytes are introduced. Additionally, recent advancements in CPSs including methods of ensuring low interfacial resistance, the respective contributions of these critical factors to the significant functional properties of CPSs, and directions for development and essential applications in the field of CPSs for LiBs are presented. Based on previous works, the perspectives put forth will aid in the design of advanced electrolytes for practical Li secondary batteries in the near future. Abstract : The recent developments and progress of flexible electrolyte membranes based on functional, hierarchitectural, and composite polymers are discussed regarding their transport mechanism, phase‐separated or mixed‐phase morphologies, ionic conductivity, thermal/mechanical stability, and battery performance. The challenges and perspectives in the design of safe, high‐performance advanced electrolyte systems for practical lithium batteries are also proposed.